A high garlic residue content liquid mulch aid and its use in liquid mulch
Patent Information
- Application Number
- CN202311438914.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-01
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-01
AI Technical Summary
显然,传统蒜渣基液体地膜中蒜渣含量越高,则蒜渣中由果糖形成的粘性物质(如果聚糖)越多,相应地传统蒜渣基液体地膜粘度也越大,也更难以喷涂
[0019] The experimental results of the effect examples show that the liquid mulch film adjuvant prepared by this invention is a stable suspension without solid-liquid stratification. This liquid mulch film adjuvant can reduce the viscosity of liquid mulch films with high garlic residue content, making the high garlic residue content liquid mulch film emulsion easier to spray and allowing for a greater spraying distance. Compared with bare soil, the soil temperature and soil moisture covered by the high garlic residue content liquid mulch film prepared using the liquid mulch film adjuvant provided by this invention are significantly increased, and the prepared high garlic residue content liquid mulch film can effectively reduce pest damage to crops. The above technical effects are due to the following working principle:
Smart Images

Figure CN117487566B_ABST
Abstract
Description
Technical fields:
[0001] This invention belongs to the field of mulch film technology, and in particular relates to a liquid mulch film additive with high garlic residue content and its application in liquid mulch film. Background technology:
[0002] Reference 1 (Geng et al, Improvement onpest resistance of sprayable mulchfilms by fully utilizing garlic residues, Journal of Cleaner Production, 2022, 364, 132596) reports a garlic residue-based liquid mulch film prepared using garlic residue as raw material. This garlic residue-based liquid mulch film not only has soil heat preservation and moisture retention functions, but also has pest control functions. However, this garlic residue-containing liquid mulch film has a high viscosity, which is not conducive to the spraying of this type of liquid mulch film. Sprayability is an important feature of liquid mulch films. Sprayable liquid mulch films are liquid before use and can be sprayed onto the soil surface by mechanical equipment. The liquid remaining on the soil surface dries naturally to form a film with heat preservation and moisture retention functions for the soil. This eliminates the complex production process such as pre-forming of mulch films involved in traditional plastic mulch films, saving manufacturing costs. At the same time, farmers can reduce labor intensity and improve construction efficiency when using sprayable liquid mulch films. In agricultural production, large-scale spraying of liquid mulch using heavy machinery promotes the intensive, large-scale, mechanized, and industrialized development of modern agriculture. Therefore, reducing the viscosity of this type of liquid mulch containing garlic residue, and ensuring its good sprayability, is necessary for its further promotion and application.
[0003] The allicin and polysaccharides in garlic residue are the main reasons for the high viscosity of the garlic residue-based liquid mulch film (referred to as traditional garlic residue-based liquid mulch film) provided in Reference 1. Allicin, scientifically known as diallyl thiosulfinate, contains a sulfhydryl group at one end of its molecule. When two sulfhydryl groups come into close contact, they form a disulfide bond (a relatively strong chemical bond). Therefore, when the garlic residue content in the liquid mulch film is high, the chances of contact and collision between the garlic residue-containing particles increase. The garlic residue-based particles easily aggregate to form a particle network through these disulfide bonds, and water molecules fill and fix in the network formed by the garlic residue-based particles. The higher the garlic residue content in the traditional garlic residue-based liquid mulch film, the larger this garlic residue-based particle network becomes, and the worse the flowability of the garlic residue-based liquid mulch film. This is one of the reasons why the high viscosity of the liquid mulch film with high garlic residue content is very high and why it is difficult to spray smoothly from the nozzle of the spray gun. In addition, garlic residue contains a relatively high amount of polysaccharides, with dried garlic residue containing approximately 20 wt% polysaccharides, far exceeding the content of allicin in the residue. The polysaccharides in garlic residue are mainly fructose. When fructose is exposed to air, it reacts with oxygen to form a viscous substance called fructan, which is the main factor contributing to the high viscosity of garlic residue-based liquid mulch. Clearly, the higher the garlic residue content in traditional garlic residue-based liquid mulch, the more viscous substances (fructan) formed from fructose are present, resulting in a correspondingly higher viscosity and greater difficulty in spraying. Therefore, it is difficult to further increase the garlic residue content in the traditional garlic residue-based liquid mulch provided in Reference 1; otherwise, the viscosity of the garlic residue-based liquid mulch will not meet the requirements for sprayability. It is important to note that reducing the viscosity of traditional garlic residue-based liquid mulch film and improving its insect resistance cannot be achieved simultaneously. If the garlic residue content in the liquid mulch film is reduced to lower its viscosity, the insect resistance will be severely weakened. This is because the insect resistance of garlic residue-based liquid mulch film is positively correlated with the content of insect-repelling components such as allicin in the garlic residue. Since liquid mulch film with high garlic residue content has stronger insect resistance and practical application value than that with low garlic residue content, developing liquid mulch film with low viscosity, easy application, and high garlic residue content is of great significance. Summary of the Invention:
[0004] To address the problems existing in the prior art, this invention provides a liquid mulch film additive with high garlic residue content and its preparation method.
[0005] The preparation steps of a liquid mulch film adjuvant with high garlic residue content are as follows:
[0006] (1) Dissolve NaOH in methanol solvent at 45-55℃ to obtain solution A, wherein the weight ratio of NaOH to methanol is 1:(5-6.7);
[0007] (2) At room temperature, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in methanol to obtain solution B, wherein the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and methanol is (1.4-2.4):1:(46-56);
[0008] (3) Add the solution B obtained in step (2) dropwise to the solution A obtained in step (1) at 45-55℃ and stirring at 2000-5000r / min. The dropwise rate is 1 drop every 3-5 seconds. When the pH of the resulting mixture is 7.5-8.5, the dropwise addition ends. Continue the reaction for 10-24 hours, and then obtain a white mixture C.
[0009] (4) Heat the white mixture C obtained in step (3) to 55-65℃, add sodium unsaturated fatty acid, and then stir at a speed of 1000-3000 r / min for 3-12 h to obtain a white mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite, wherein the weight ratio of the white mixture C obtained in step (3) to sodium unsaturated fatty acid is (6-15):(0.28-0.58);
[0010] (5) Filter the mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite obtained in step (4), and wash the filtered gel with methanol solvent 3-5 times to obtain white unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E, wherein the weight ratio of mixture D to methanol solvent is 1:3.
[0011] (6) Dissolve carboxyl-modified polyvinyl alcohol in water at room temperature to obtain solution F. Adjust the pH of solution F to 6.5-7.5 with sodium hydroxide solution. Then, add the unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E obtained in step (4) to solution F under stirring conditions at 20-35℃. The stirring speed is 2500-5000 r / min. After stirring for 6-24 h, a colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite intercalated organic-inorganic composite is obtained. The weight ratio of carboxyl-modified polyvinyl alcohol to water in solution F is (0.5-1.5):100, the mass percentage concentration of sodium hydroxide solution is 2%-5%, and the weight ratio of solution F to gel E is (1.5-3.5):1.
[0012] (7) The colloidal suspension G of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered organic-inorganic composite obtained in step (6) is stirred with α-amylase at room temperature for 1-5 hours at a stirring speed of 100-500 r / min. The resulting colloidal suspension is a liquid mulch film adjuvant with high garlic residue content. The mass ratio of colloidal suspension G to amylase is (18-21):1.
[0013] Another object of the present invention is to prepare a liquid mulch film with high garlic residue content using a liquid mulch film additive with high garlic residue content. The preparation method is characterized by using raw materials comprising: a liquid mulch film additive with high garlic residue content, garlic residue slurry, starch slurry, and a mixture of acrylic monomers. The preparation steps are as follows:
[0014] (S1) Mix the high garlic residue content liquid mulch film adjuvant with garlic residue slurry at 55-65℃ for 0.5-1.5h at a speed of 50-150r / min. Then mix the resulting mixture with starch slurry and continue stirring at 55-65℃ for 1.5-3h at a speed of 50-150r / min to obtain slurry J. The garlic residue slurry contains garlic residue particles smaller than 10 mesh, and the weight content of garlic residue in the garlic residue slurry is 65-75%. The starch slurry is prepared from soluble starch, and the mass ratio between soluble starch and water is (0.15-0.21):1. The mass ratio between the high garlic residue content liquid mulch film adjuvant, garlic residue slurry, and starch slurry is (0.08-0.15):(0.9-1.1):1.
[0015] (S2) The J slurry obtained in step (S1) is mixed with an acrylic monomer mixture, an emulsifier and water. The resulting mixture is pre-emulsified at 70-80℃ and a stirring speed of 1500-3500r / min for 30-120min to obtain a pre-emulsified mixture K. The mass ratio of the J slurry, the acrylic monomer mixture, the emulsifier and water is (15-22):(4-10):1:(14-28). The acrylic monomer mixture includes butyl acrylate, methyl methacrylate and acrylic acid, and the mass ratio of the three is (6.5-7.5):(1.5-2.5):1. The emulsifier is a mixture of a reactive emulsifier and octylphenol polyoxyethylene ether (10), and the mass ratio of the two is 1:(2.5-3.5). The reactive emulsifier is of type LRS-10.
[0016] (S3) While stirring at 75-90℃, add the initiator aqueous solution dropwise to the pre-emulsified mixture K obtained in step (S2) at a rate of 0.2-1.5 mL / min. The stirring speed is 250-500 r / min. After the initiator is added, continue the reaction for 2-8 hours. The mass ratio between the pre-emulsified mixture K and the initiator aqueous solution is (6.5-8.5):1. Then, cool the reaction system to room temperature and adjust the pH of the system to 6.8-7.5 with ammonia water to obtain a liquid mulch film emulsion with high garlic residue content. The initiator aqueous solution is a potassium persulfate or ammonium persulfate aqueous solution, wherein the mass concentration of potassium persulfate or ammonium persulfate is 3.5-5.5%; the mass percentage concentration of the ammonia water is 25%.
[0017] The water used in the preparation methods described above is all deionized water.
[0018] The present invention differs from the prior art in that it achieves the following technical effects:
[0019] The experimental results of the effect examples show that the liquid mulch film adjuvant prepared by this invention is a stable suspension without solid-liquid stratification. This liquid mulch film adjuvant can reduce the viscosity of liquid mulch films with high garlic residue content, making the high garlic residue content liquid mulch film emulsion easier to spray and allowing for a greater spraying distance. Compared with bare soil, the soil temperature and soil moisture covered by the high garlic residue content liquid mulch film prepared using the liquid mulch film adjuvant provided by this invention are significantly increased, and the prepared high garlic residue content liquid mulch film can effectively reduce pest damage to crops. The above technical effects are due to the following working principle:
[0020] In the preparation steps of the liquid mulch film additive, steps (1)-(3) involve preparing a mixture C of methoxylated magnesium aluminum hydrotalcite compounds in methanol solvent using magnesium nitrate hexahydrate and aluminum nitrate nonahydrate as raw materials. The classic hydrotalcite is magnesium aluminum carbonate type hydrotalcite, whose structure is very similar to the layered structure of brucite [Mg(OH)2]. The hydrotalcite layers are formed by MgO6 octahedra sharing common edges to form unit layers, with MgO6 on the layers... 2+ Can be used by Al within a certain range 3+ Isomorphic substitution results in positively charged layers, and CO3 between the layers... 2- The positive charge on the layers balances the overall electroneutrality of the magnesium aluminum carbonate-type hydrotalcite. In steps (1)-(3) of this invention, methanol molecules in the reaction system react with the metal hydroxyl groups (M-OH) on the magnesium aluminum hydrotalcite layers under the action of sodium hydroxide to form M-OCH3 groups, while NO3 is present between the layers. - Anions are used to balance the positive charge on the hydrotalcite layers.
[0021] In steps (4) and (5) of the preparation of liquid mulch film additives, the methoxy magnesium aluminum hydrotalcite prepared in steps (1)-(3) undergoes an interlayer ion exchange reaction with sodium unsaturated fatty acids under stirring conditions, that is, the unsaturated fatty acid anions replace the NO3 in the interlayer of the methoxy magnesium aluminum hydrotalcite. -Anions enter the interlayer space, yielding a mixed solution D containing unsaturated fatty acid-methoxymagnesium aluminum hydrotalcite. Solution D is then washed and filtered with methanol to obtain a colloidal unsaturated fatty acid-methoxymagnesium aluminum hydrotalcite compound E. Sodium unsaturated fatty acids dissolve in water and ionize to release unsaturated fatty acid anions. These anions are characterized by a carboxyl group at one end and an aliphatic hydrocarbon chain at the other. Therefore, the unsaturated fatty acid anions in the interlayer space increase the distance between the magnesium aluminum inorganic layers and the intercalation space between them. This weakens the interaction between the inorganic layers, which facilitates ion exchange reactions between other anions and the interlayer unsaturated fatty acid anions to obtain new intercalated hydrotalcite compounds.
[0022] In step (6) of the preparation of the liquid mulch film additive, while the unsaturated fatty acid-methoxymagnesium aluminum hydrotalcite colloid E undergoes hydrolysis with water, it also undergoes an interlayer ion exchange reaction with negatively charged carboxyl-modified polyvinyl alcohol (the negative charge is caused by the ionization of protons from the carboxyl group). The M-OCH3 group in the unsaturated fatty acid-methoxymagnesium aluminum hydrotalcite colloid E readily hydrolyzes in water to generate M-OH. This hydrolysis reaction is relatively rapid and vigorous, and the energy released by the reaction can instantly break down the colloid into very small colloidal particles, which can be suspended in the aqueous solution. In the hydrolysis reaction of unsaturated fatty acid-methoxy magnesium aluminum layered double hydroxide (LDH) colloids, methanol molecules formed by the hydrolysis of the M-OCH3 groups detach from the layers. Simultaneously, the interaction between the inorganic layers of the magnesium aluminum LDH is further weakened. This facilitates interlayer ion exchange between the negatively charged carboxyl-modified polyvinyl alcohol (PVA) and the unsaturated fatty acid anions between the inorganic layers of the magnesium aluminum LDH. This results in the carboxyl-modified PVA embedding into the spaces between the magnesium aluminum LDH layers, forming a carboxyl-modified PVA-magnesium aluminum LDH intercalation complex. The colloidal particles composed of this intercalation complex can be stably suspended in aqueous solution. In the aforementioned interlayer ion exchange reaction, the unsaturated fatty acid anions exchanged from the interlayers have a certain emulsifying effect, which also helps the carboxyl-modified PVA-magnesium aluminum LDH intercalation complex to remain stably suspended in aqueous solution, thus obtaining a colloidal suspension G containing the carboxyl-modified PVA-magnesium aluminum LDH intercalation complex. Furthermore, the unsaturated fatty acid ions exchanged between the layers can react with glucose molecules hydrolyzed from starch in subsequent treatments through esterification to form glucose-unsaturated fatty acid esters with surfactant functions. This also helps to reduce the viscosity of liquid mulch films with high garlic residue content.
[0023] In step (7) of the preparation of the high garlic residue content liquid mulch adjuvant, the hydroxyl and carboxyl groups in the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered intercalation complex can interact with the carboxyl and amino groups on the end groups of α-amylase molecules through hydrogen bonds. Furthermore, the negative charge of the amylase molecules can interact with the positive charge on the hydrotalcite layers, thereby encapsulating and immobilizing the α-amylase within a three-dimensional network composed of carboxyl-modified polyvinyl alcohol polymer chains and hydrotalcite inorganic layers. This three-dimensional network is hydrophilic, excluding the fat-soluble and hydrophobic allicin from the hydrophilic network, preventing allicin from damaging the α-amylase encapsulated within the hydrophilic network. Simultaneously, hydrophilic polysaccharide molecules can enter this hydrophilic network, contact the amylase within the network, and be degraded into smaller sugar molecules by the amylase. In addition, the prepared liquid mulch adjuvant is a stable colloidal suspension, which is not prone to solid-liquid stratification and will not cause solid-liquid stratification in the subsequently prepared high garlic residue content liquid mulch emulsion. Solid-liquid stratification reduces the sprayability of liquid mulch film emulsions and the uniformity of their distribution on the soil surface. Therefore, mulch film emulsions with solid-liquid stratification are not suitable for practical applications.
[0024] In the preparation step (S1) of the high garlic residue content liquid mulch film, the aforementioned high garlic residue content liquid mulch film adjuvant is first mixed with the garlic residue slurry. The amylase in this liquid mulch film adjuvant, at a suitable temperature, can degrade the fructose polymer in the garlic residue slurry into small molecule sugars through enzymatic hydrolysis. Simultaneously, the liquid mulch film adjuvant adheres to the surface of the garlic residue particles, separating them from each other and preventing the particles from agglomerating through disulfide bonds formed by allicin. In other words, when the garlic residue content is high, the garlic residue particles in the slurry treated with the liquid mulch film adjuvant are less prone to agglomeration. Since the viscous polysaccharides (fructans) in the garlic residue have also been degraded, the viscosity of the garlic residue slurry treated with the liquid mulch film adjuvant is reduced. When garlic residue slurry treated with liquid mulch film additives is mixed with starch slurry, the amylase in the liquid mulch film additives adhering to the garlic residue particles can continue to degrade the polysaccharides in the starch through enzymatic hydrolysis, thereby reducing the viscosity of both garlic residue slurry and starch slurry. This is beneficial for reducing the viscosity of the subsequently prepared liquid mulch film emulsion with high garlic residue content.
[0025] In the preparation step (S2) of liquid mulch film with high garlic residue content, garlic residue slurry and starch slurry treated with liquid mulch film additives and acrylic monomer mixture form pre-emulsified mixture K in the presence of emulsifier. In each emulsion droplet of pre-emulsified mixture K, the carbonyl and carboxyl polar groups of acrylic acid and butyl acrylate in the acrylic monomer mixture can form hydrogen bonds with the hydroxyl and other polar groups in garlic residue slurry and starch slurry, thereby making the components uniformly combined with each other at the molecular level through hydrogen bonding.
[0026] In step (S3) of preparing high-garlic-residue liquid mulch film, an initiator is added to cause molecules with double bonds, organic molecules with hydroxyl and carboxyl groups in the pre-emulsion K to form free radicals. These free radicals copolymerize to form a mulch film emulsion with a three-dimensional network structure composed of interwoven polymer chains. Due to the degradation of viscous polysaccharide molecules in the mulch film emulsion into smaller sugar molecules, and the barrier effect of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered intercalation complex in the liquid mulch film adjuvant on the aggregation of garlic residue particles, the viscosity of this high-garlic-residue liquid mulch film emulsion is suitable and can be smoothly sprayed out by the spray gun. Attached Figure Description
[0027] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0028] Figure 1 In the diagram, a represents the magnesium-aluminum hydrotalcite prepared in Comparative Example 6 of this invention, b represents the methoxy magnesium-aluminum hydrotalcite prepared in Example 3, c represents the unsaturated fatty acid-methoxy magnesium-aluminum hydrotalcite, and d represents the X-ray powder diffraction pattern of carboxyl-modified polyvinyl alcohol-magnesium-aluminum hydrotalcite.
[0029] Figure 2 This is a process flow diagram of the preparation process of a liquid mulch film additive with high garlic residue content according to the present invention.
[0030] Figure 3 This is a flowchart illustrating the preparation process of the liquid mulch film with high garlic residue content according to the present invention. Detailed Implementation
[0031] The above and other technical features and advantages of the present invention will be described in more detail below with reference to the embodiments. Unless otherwise specified, all chemical raw materials used in the following embodiments are commercially available, chemically pure reagents; sodium unsaturated fatty acid, CAS number 67701-11-5, purchased from Aladdin Biochemical Technology Co., Ltd.; carboxyl-modified polyvinyl alcohol, model KL-318, brand Kuraray, Japan, purchased from Shanghai Jinsuyu Plastic Raw Materials Co., Ltd.; α-amylase, enzyme activity of 20,000 u / g, food grade, purchased from Jiangsu Ruicheng Biotechnology Co., Ltd.; soluble starch, analytical grade, purchased from Shanghai Zhanyun Chemical Co., Ltd.; butyl acrylate, methyl methacrylate, acrylic acid with a purity of 99% and ammonia water with a concentration of 25% were all purchased from Damao Chemical Reagent Co., Ltd. (Tianjin, China); 99% pure reactive emulsifier (model LRS-10) and 99% pure octylphenol polyoxyethylene ether (10) (OP-10) were purchased from Nanjing Qicheng New Material Co., Ltd. Potassium persulfate and ammonium persulfate with a purity of 99.5% were purchased from Lingfeng Chemical Reagent Co., Ltd. (Shanghai, China).
[0032] Example 1
[0033] (1) Dissolve NaOH in methanol solvent at 45℃ to obtain solution A, wherein the weight ratio of NaOH to methanol is 1:5;
[0034] (2) At room temperature, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in methanol solvent to obtain solution B, wherein the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and methanol is 1.4:1:46;
[0035] (3) The solution B obtained in step (2) is added dropwise to the solution A obtained in step (1) at 45°C and stirring at 5000 r / min. The dropwise rate is 1 drop every 3 seconds. When the pH of the resulting mixture is 7.5, the dropwise addition is stopped. The reaction continues for 10 h, and then a white mixture C is obtained.
[0036] (4) Heat the white mixture C obtained in step (3) to 55°C, add sodium unsaturated fatty acid, and then stir at a stirring speed of 3000 r / min for 12 h to obtain a white mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite, wherein the weight ratio of the white mixture C obtained in step (3) to sodium unsaturated fatty acid is 6:0.28.
[0037] (5) Filter the mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite obtained in step (4), and wash the filtered gel with methanol solvent three times to obtain white unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E, wherein the weight ratio of mixture D to methanol solvent is 1:3.
[0038] (6) Dissolve carboxyl-modified polyvinyl alcohol in water at room temperature to obtain solution F. Then adjust the pH of solution F to 6.5 with sodium hydroxide solution. Then add the unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E obtained in step (4) to solution F under stirring conditions at 20°C. The stirring speed is 2500 r / min. After stirring for 6 h, a colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite intercalated organic-inorganic complex is obtained. The weight ratio of carboxyl-modified polyvinyl alcohol to water in solution F is 0.5:100, the mass percentage concentration of sodium hydroxide solution is 2%, and the weight ratio of solution F to gel E is 1.5:1.
[0039] (7) The colloidal suspension G of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered organic-inorganic composite obtained in step (6) is stirred with α-amylase at room temperature for 1 hour at a stirring speed of 100 r / min. The resulting colloidal suspension is a liquid mulch film adjuvant with high garlic residue content. The mass ratio of colloidal suspension G to amylase is 18:1.
[0040] Example 2
[0041] (1) Dissolve NaOH in methanol solvent at 47℃ to obtain solution A, wherein the weight ratio of NaOH to methanol is 1:5.4;
[0042] (2) At room temperature, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in methanol solvent to obtain solution B, wherein the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and methanol is 1.65:1:48.5;
[0043] (3) The solution B obtained in step (2) is added dropwise to the solution A obtained in step (1) at 47°C and stirring at 4250 r / min. The drop rate is 1 drop every 3 seconds. The addition ends when the pH of the resulting mixture is 7.7. The reaction continues for 13 hours, and then a white mixture C is obtained.
[0044] (4) Heat the white mixture C obtained in step (3) to 57°C, add sodium unsaturated fatty acid, and then stir at a stirring speed of 2500 r / min for 10 h to obtain a white mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite, wherein the weight ratio of the white mixture C obtained in step (3) to sodium unsaturated fatty acid is 8:0.34.
[0045] (5) Filter the mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite obtained in step (4), and wash the filtered gel with methanol solvent three times to obtain white unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E, wherein the weight ratio of mixture D to methanol solvent is 1:3.
[0046] (6) Dissolve carboxyl-modified polyvinyl alcohol in water at room temperature to obtain solution F. Then adjust the pH of solution F to 6.7 with sodium hydroxide solution. Then add the unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E obtained in step (4) to solution F under stirring conditions at 24℃. The stirring speed is 3200 r / min. After stirring for 10 h, a colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite intercalated organic-inorganic complex is obtained. The weight ratio of carboxyl-modified polyvinyl alcohol to water in solution F is 0.8:100, the mass percentage concentration of sodium hydroxide solution is 2%, and the weight ratio of solution F to gel E is 2.0:1.
[0047] (7) The colloidal suspension G of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered organic-inorganic complex obtained in step (6) is stirred with α-amylase at room temperature for 2 hours at a stirring speed of 200 r / min. The resulting colloidal suspension is a liquid mulch film adjuvant with high garlic residue content. The mass ratio of colloidal suspension G to amylase is 19:1.
[0048] Example 3
[0049] (1) Dissolve NaOH in methanol solvent at 50℃ to obtain solution A, wherein the weight ratio of NaOH to methanol is 1:5.8;
[0050] (2) At room temperature, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in methanol solvent to obtain solution B, wherein the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and methanol is 1.9:1:51;
[0051] (3) The solution B obtained in step (2) is added dropwise to the solution A obtained in step (1) at 50°C and stirring at 3500 r / min. The dropwise rate is 1 drop every 4 seconds. When the pH of the resulting mixture is 8.0, the dropwise addition ends. The reaction continues for 17 h, and then a white mixture C is obtained.
[0052] (4) Heat the white mixture C obtained in step (3) to 60°C, add sodium unsaturated fatty acid, and then stir at a stirring speed of 2000 r / min for 8 h to obtain a white mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite, wherein the weight ratio of the white mixture C obtained in step (3) to sodium unsaturated fatty acid is 10:0.4.
[0053] (5) Filter the mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite obtained in step (4), and wash the filtered gel with methanol solvent 4 times to obtain white unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E, wherein the weight ratio of mixture D to methanol solvent is 1:3.
[0054] (6) Dissolve carboxyl-modified polyvinyl alcohol in water at room temperature to obtain solution F. Then adjust the pH of solution F to 7.0 with sodium hydroxide solution. Then add the unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E obtained in step (4) to solution F under stirring conditions at 28℃. The stirring speed is 3800 r / min. After stirring for 15 h, a colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite intercalated organic-inorganic complex is obtained. The weight ratio of carboxyl-modified polyvinyl alcohol to water in solution F is 1.0:100, the mass percentage concentration of sodium hydroxide solution is 3%, and the weight ratio of solution F to gel E is 2.5:1.
[0055] (7) The colloidal suspension G of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered organic-inorganic complex obtained in step (6) is stirred with α-amylase at room temperature for 3 hours at a stirring speed of 300 r / min. The resulting colloidal suspension is a liquid mulch film adjuvant with high garlic residue content. The mass ratio of colloidal suspension G to amylase is 19.5:1.
[0056] Example 4
[0057] (1) Dissolve NaOH in methanol at 53℃ to obtain solution A, wherein the weight ratio of NaOH to methanol is 1:6.3;
[0058] (2) At room temperature, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in methanol solvent to obtain solution B, wherein the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and methanol is 2.15:1:53.5;
[0059] (3) The solution B obtained in step (2) is added dropwise to the solution A obtained in step (1) at 53°C and stirring at 2750 r / min. The dropwise rate is 1 drop every 4 seconds. When the pH of the resulting mixture is 8.2, the dropwise addition is stopped. The reaction continues for 21 h, and then a white mixture C is obtained.
[0060] (4) Heat the white mixture C obtained in step (3) to 63°C, add sodium unsaturated fatty acid, and then stir at a stirring speed of 1500 r / min for 6 h to obtain a white mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite, wherein the weight ratio of the white mixture C obtained in step (3) to sodium unsaturated fatty acid is 13:0.5.
[0061] (5) Filter the mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite obtained in step (4), and wash the filtered gel with methanol solvent 4 times to obtain white unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E, wherein the weight ratio of mixture D to methanol solvent is 1:3.
[0062] (6) Dissolve carboxyl-modified polyvinyl alcohol in water at room temperature to obtain solution F. Then adjust the pH of solution F to 7.3 with sodium hydroxide solution. Then add the unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E obtained in step (4) to solution F under stirring conditions at 32℃. The stirring speed is 4500 r / min. After stirring for 20 h, a colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite intercalated organic-inorganic complex is obtained. The weight ratio of carboxyl-modified polyvinyl alcohol to water in solution F is 1.3:100, the mass percentage concentration of sodium hydroxide solution is 4%, and the weight ratio of solution F to gel E is 3.0:1.
[0063] (7) The colloidal suspension G of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered organic-inorganic complex obtained in step (6) is stirred with α-amylase at room temperature for 4 hours at a stirring speed of 400 r / min. The resulting colloidal suspension is a liquid mulch film adjuvant with high garlic residue content. The mass ratio of colloidal suspension G to amylase is 20:1.
[0064] Example 5
[0065] (1) Dissolve NaOH in methanol solvent at 55℃ to obtain solution A, wherein the weight ratio of NaOH to methanol is 1:6.7;
[0066] (2) At room temperature, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in methanol solvent to obtain solution B, wherein the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and methanol is 2.4:1:56.
[0067] (3) The solution B obtained in step (2) is added dropwise to the solution A obtained in step (1) at 55°C and stirring at 2000 r / min. The dropwise rate is 1 drop every 5 seconds. When the pH of the resulting mixture is 8.5, the dropwise addition ends. The reaction continues for 24 hours, and then a white mixture C is obtained.
[0068] (4) Heat the white mixture C obtained in step (3) to 65°C, add sodium unsaturated fatty acid, and then stir at a stirring speed of 1000 r / min for 3 h to obtain a white mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite, wherein the weight ratio of the white mixture C obtained in step (3) to sodium unsaturated fatty acid is 15:0.58.
[0069] (5) Filter the mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite obtained in step (4), and wash the filtered gel with methanol solvent 5 times to obtain white unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E, wherein the weight ratio of mixture D to methanol solvent is 1:3.
[0070] (6) Dissolve carboxyl-modified polyvinyl alcohol in water at room temperature to obtain solution F. Then adjust the pH of solution F to 7.5 with sodium hydroxide solution. Then add the unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite colloid E obtained in step (4) to solution F under stirring conditions at 35°C. The stirring speed is 5000 r / min. After stirring for 24 h, a colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered intercalation organic-inorganic complex is obtained. The weight ratio of carboxyl-modified polyvinyl alcohol to water in solution F is 1.5:100, the mass percentage concentration of sodium hydroxide solution is 5%, and the weight ratio of solution F to colloid E is 3.5:1.
[0071] (7) The colloidal suspension G of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered organic-inorganic composite obtained in step (6) is stirred with α-amylase at room temperature for 5 hours at a stirring speed of 500 r / min. The resulting colloidal suspension is a liquid mulch film adjuvant with high garlic residue content. The mass ratio of colloidal suspension G to amylase is 21:1.
[0072] Comparative Example 6
[0073] The difference between this embodiment and Example 3 is that in this embodiment, methanol solvent is not used in steps (1)-(5), but deionized water is used instead of methanol, and the amount of water is the same as that of methanol. The other preparation steps and reagent amounts are the same as in Example 3. The specific preparation steps are as follows:
[0074] (1) Dissolve NaOH in an aqueous solvent at 50℃ to obtain solution A, wherein the weight ratio of NaOH to water is 1:5.8;
[0075] (2) At room temperature, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in an aqueous solvent to obtain solution B, wherein the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and water is 1.9:1:51;
[0076] (3) The solution B obtained in step (2) is added dropwise to the solution A obtained in step (1) at 50°C and stirring at 3500 r / min. The dropwise rate is 1 drop every 4 seconds. When the pH of the resulting mixture is 8.0, the dropwise addition ends. The reaction continues for 17 h, and then a white mixture C is obtained.
[0077] (4) Heat the white mixture C obtained in step (3) to 60°C, add sodium unsaturated fatty acid, and then stir at a speed of 2000 r / min for 8 hours to obtain a white mixture D containing unsaturated fatty acid-magnesium aluminum hydrotalcite. The weight ratio of the white mixture C obtained in step (3) to sodium unsaturated fatty acid is 10:0.4.
[0078] (5) Filter the mixture D containing unsaturated fatty acids-magnesium aluminum hydrotalcite obtained in step (4), and wash the filtered precipitate repeatedly with water solvent 4 times to obtain white unsaturated fatty acids-magnesium aluminum hydrotalcite gel E, wherein the weight ratio of mixture D to water solvent is 1:3.
[0079] Steps (6) and (7) in this embodiment are the same as steps (6) and (7) in embodiment (3).
[0080] The white mixture C obtained in step (3) of this embodiment was filtered and washed three times with 50 ml of water. The precipitate after washing was dried to constant weight in a vacuum drying oven at 60°C to obtain dried magnesium aluminum hydrotalcite. In Example 3, the mixture C obtained in step (3) was filtered, washed with methanol solvent, and vacuum dried to obtain methoxy magnesium aluminum hydrotalcite. The colloidal substance E obtained in step (5) was vacuum dried to obtain unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite. The colloidal suspension G obtained in step (6) was filtered, washed with deionized water, and vacuum dried to obtain a carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered organic-inorganic composite. The samples obtained above were ground into powder and then subjected to X-ray powder diffraction characterization test (X-ray powder diffraction was performed on a Rigaku D / MAX X-ray diffractometer, CuKα ( (Pipe voltage 40.0kV, pipe current 30.0mA), test results are attached. Figure 1 As shown.
[0081] Appendix Figure 1The image shows X-ray powder diffraction patterns of the magnesium-aluminum hydrotalcite prepared in step (3) of Comparative Example 6 and the methoxy magnesium-aluminum hydrotalcite, unsaturated fatty acid-methoxy magnesium-aluminum hydrotalcite, and carboxyl-modified polyvinyl alcohol-magnesium-aluminum hydrotalcite prepared in Example 3 of this invention. Compared to magnesium-aluminum hydrotalcite, the first diffraction peak of the methoxy magnesium-aluminum hydrotalcite shifts towards the small-angle diffraction direction. This is because in Example 3, magnesium-aluminum hydrotalcite was prepared in methanol solvent, and the methoxy groups in methanol were grafted onto the layers of the magnesium-aluminum hydrotalcite, leading to an increase in the interlayer spacing. Compared to methoxy magnesium-aluminum hydrotalcite, the first diffraction peak of the unsaturated fatty acid-methoxy magnesium-aluminum hydrotalcite shifts towards the small-angle diffraction direction. This is because negatively charged unsaturated fatty acid ions are embedded into the positively charged interlayers of the magnesium-aluminum hydrotalcite, further increasing the interlayer spacing. Compared to unsaturated fatty acid-methoxy magnesium aluminum layered double hydroxides, the diffraction peak shapes of carboxyl-modified polyvinyl alcohol-magnesium aluminum layered double hydroxides changed, and the position of the first diffraction peak shifted. This is because the negatively charged carboxyl-modified polyvinyl alcohol replaced the unsaturated fatty acid ions and entered the inorganic interlayer. At the same time, the methoxy groups grafted onto the inorganic interlayer were also removed from the interlayer surface during the hydrolysis reaction. This resulted in changes in the interlayer structure of carboxyl-modified polyvinyl alcohol-magnesium aluminum layered double hydroxides compared to the interlayer structure of unsaturated fatty acid-methoxy magnesium aluminum layered double hydroxides.
[0082] Comparative Example 7
[0083] The difference between this embodiment and Example 3 is that this embodiment omits step (4). Instead, in step (5), the white mixture C obtained in step (3) is used instead of the mixture D in step (5) of Example (3). After filtration and washing with methanol four times, a gel-like substance E is obtained. This gel-like substance E is then used for subsequent reactions. That is, the reaction between sodium unsaturated fatty acids and methoxy magnesium aluminum hydrotalcite is not used, and the preparation steps also do not use unsaturated fatty acids-methoxy magnesium aluminum hydrotalcite. The other preparation steps and reagent amounts are the same as in Example 3.
[0084] Comparative Example 8
[0085] The difference between this embodiment and Example 3 is that carboxyl-modified polyvinyl alcohol is not used in preparation steps (6) and (7) of this embodiment, that is, the colloidal suspension of carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite is not prepared. The other preparation steps and reagent amounts are the same as in Example 3. Steps (6) and (7) of this embodiment are as follows:
[0086] (6) The unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite colloid E obtained in step (4) was added to deionized water at 28℃ and under stirring conditions. The stirring speed was 3800 r / min. After stirring for 15 h, a colloidal suspension G was obtained, in which the weight ratio of deionized water to colloid E was 2.5:1.
[0087] (7) The colloidal suspension G obtained in step (6) is stirred with α-amylase at room temperature for 3 hours at a stirring speed of 300 r / min. The resulting colloidal suspension is a liquid mulch film adjuvant, wherein the mass ratio of colloidal suspension G to amylase is 19.5:1.
[0088] Comparative Example 9
[0089] The difference between this embodiment and Example 3 is that in step (7) of this embodiment, the mass ratio of the colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite to α-amylase is 16:1, which is not within the scope of claims (18-21):1. The other preparation steps and reagent dosages are the same as in Example 3.
[0090] Comparative Example 10
[0091] The difference between this embodiment and Embodiment 3 is that the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and methanol in step (2) of this embodiment is 1.9:0.6:51, which is outside the range of (1.4-2.4):1:(46-56) in the claims, meaning the amount of aluminum nitrate nonahydrate used is smaller. The other preparation steps and reagent amounts are the same as in Embodiment 3.
[0092] Application Example 11
[0093] The liquid mulch film additive prepared in Example 3 was used to prepare a liquid mulch film with high garlic residue content according to the following steps.
[0094] (S1) A liquid mulch film additive with high garlic residue content is stirred with garlic residue slurry at 55°C for 0.5 hours at a speed of 50 r / min. The resulting mixture is then mixed with starch slurry and stirred at 55°C for another 1.5 hours at a speed of 50 r / min to obtain slurry J. The garlic residue slurry contains garlic residue particles smaller than 10 mesh, and the weight content of garlic residue in the slurry is 65%. The starch slurry is prepared from soluble starch, and the mass ratio of soluble starch to water is 0.15:1. The mass ratio of the garlic residue-based liquid mulch film additive, garlic residue slurry, and starch slurry is 0.08:0.9:1.
[0095] (S2) The J slurry obtained in step (S1) is mixed with an acrylic monomer mixture, an emulsifier and water. The resulting mixture is pre-emulsified for 30 minutes at 70°C and a stirring speed of 1500 r / min to obtain a pre-emulsified mixture K. The mass ratio of the J slurry, the acrylic monomer mixture, the emulsifier and water is 15:4:1:14. The acrylic monomer mixture includes butyl acrylate, methyl methacrylate and acrylic acid, with a mass ratio of 6.5:1.5:1. The emulsifier is a mixture of a reactive emulsifier and octylphenol polyoxyethylene ether (10), with a mass ratio of 1:2.5. The reactive emulsifier is of type LRS-10.
[0096] (S3) While stirring at 75℃, add the initiator aqueous solution dropwise to the pre-emulsified mixture K obtained in step (S2) at a rate of 0.2 mL / min. The stirring speed is 250 r / min. After the initiator is added, continue the reaction for 2 hours. The mass ratio between the pre-emulsified mixture K and the initiator aqueous solution is 6.5:1. Then, cool the reaction system to room temperature and adjust the pH of the system to 6.8 with ammonia water to obtain an emulsion of liquid mulch film with high garlic residue content. The initiator aqueous solution is an ammonium persulfate aqueous solution with a mass concentration of 3.5% and the ammonia water has a mass percentage concentration of 25%.
[0097] Application Example 12
[0098] The liquid mulch film additive prepared in Example 3 was used to prepare a liquid mulch film with high garlic residue content according to the following steps.
[0099] (S1) The high garlic residue content liquid mulch adjuvant and garlic residue slurry are stirred at 60°C for 1.0 h at a speed of 100 r / min. Then, the resulting mixture is mixed with starch slurry and stirred at 60°C for 2.25 h at a stirring speed of 100 r / min to obtain slurry J. The garlic residue slurry contains garlic residue particles smaller than 10 mesh, and the weight content of garlic residue in the garlic residue slurry is 70%. The starch slurry is prepared from soluble starch, and the mass ratio between soluble starch and water is 0.18:1. The mass ratio between the high garlic residue content liquid mulch adjuvant, garlic residue slurry and starch slurry is 0.12:1:1.
[0100] (S2) The J slurry obtained in step (S1) is mixed with an acrylic monomer mixture, an emulsifier and water. The resulting mixture is pre-emulsified for 75 min at 75°C and a stirring speed of 2500 r / min to obtain a pre-emulsified mixture K. The mass ratio of the J slurry, the acrylic monomer mixture, the emulsifier and water is 19:7:1:21. The acrylic monomer mixture includes butyl acrylate, methyl methacrylate and acrylic acid, with a mass ratio of 7.0:2.0:1. The emulsifier is a mixture of a reactive emulsifier and octylphenol polyoxyethylene ether (10), with a mass ratio of 1:3.0. The reactive emulsifier is of type LRS-10.
[0101] (S3) While stirring at 83℃, an initiator aqueous solution is added dropwise to the pre-emulsified mixture K obtained in step (S2) at a rate of 0.8 mL / min. The stirring speed is 370 r / min. After the initiator is added, the reaction continues for 5 hours. The mass ratio between the pre-emulsified mixture K and the initiator aqueous solution is 7.5:1. Then, the reaction system is cooled to room temperature, and the pH of the system is adjusted to 7.0 with ammonia water to obtain an emulsion of liquid mulch film with high garlic residue content. The initiator aqueous solution is a potassium persulfate aqueous solution with a mass concentration of 4.5% and the ammonia water has a mass percentage concentration of 25%.
[0102] Application Example 13
[0103] The liquid mulch film additive prepared in Example 3 was used to prepare a liquid mulch film with high garlic residue content according to the following steps.
[0104] (S1) A liquid mulch film additive with high garlic residue content is stirred with garlic residue slurry at 65°C for 1.5 hours at a speed of 150 r / min. The resulting mixture is then mixed with starch slurry and stirred at 65°C for 3 hours at a speed of 150 r / min to obtain slurry J. The garlic residue slurry contains garlic residue particles smaller than 10 mesh, and the weight content of garlic residue in the slurry is 75%. The starch slurry is prepared from soluble starch, and the mass ratio between soluble starch and water is 0.21:1. The mass ratio between the garlic residue-based liquid mulch film additive, garlic residue slurry, and starch slurry is 0.15:1.1:1.
[0105] (S2) The J slurry obtained in step (S1) is mixed with an acrylic monomer mixture, an emulsifier and water. The resulting mixture is pre-emulsified for 120 minutes at 80°C and a stirring speed of 3500 r / min to obtain a pre-emulsified mixture K. The mass ratio of the J slurry, the acrylic monomer mixture, the emulsifier and water is 22:10:1:28. The acrylic monomer mixture includes butyl acrylate, methyl methacrylate and acrylic acid, with a mass ratio of 7.5:2.5:1. The emulsifier is a mixture of a reactive emulsifier and octylphenol polyoxyethylene ether (10), with a mass ratio of 1:3.5. The reactive emulsifier is of type LRS-10.
[0106] (S3) While stirring at 90℃, an initiator aqueous solution is added dropwise to the pre-emulsified mixture K obtained in step (S2) at a rate of 1.5 mL / min. The stirring speed is 500 r / min. After the initiator is added, the reaction continues for 8 hours. The mass ratio between the pre-emulsified mixture K and the initiator aqueous solution is 8.5:1. Then, the reaction system is cooled to room temperature, and the pH of the system is adjusted to 7.5 with ammonia water to obtain an emulsion of liquid mulch film with high garlic residue content. The initiator aqueous solution is a potassium persulfate aqueous solution with a mass concentration of 5.5% and the ammonia water has a mass percentage concentration of 25%.
[0107] Application Example 14
[0108] The difference between this embodiment and application embodiment 12 is that in step (S1) of this embodiment, the mass ratio between the high garlic residue content liquid mulch adjuvant prepared in embodiment 3, the garlic residue slurry, and the starch slurry is 0.06:1:1, which is not within the scope of the claims (0.08-0.15):(0.9-1.1):1. All other preparation steps and reagent dosages are the same as in application embodiment 12.
[0109] In addition, for comparison, a mulch film emulsion was also prepared according to the preparation steps and reagent dosages of Application Example 12 without using any liquid mulch film adjuvants (i.e., the mass ratio between high garlic residue liquid mulch film adjuvant, garlic residue slurry and starch slurry was 0:1:1).
[0110] Application Example 15
[0111] The liquid mulch adjuvants (or samples) prepared in Examples 1, 2, 4, 5 and Comparative Examples 6-10 were used to prepare liquid mulch with high garlic residue content according to the steps and reagent dosages in Application Example 12.
[0112] Effect Example
[0113] 1. In this embodiment, the emulsion stability of the liquid mulch film adjuvants prepared in Examples 1-5 and the samples prepared in Examples 6-10 were tested.
[0114] Observe whether the sample will separate into layers within 30 days. If the sample does not separate into layers, it indicates that the liquid is stable and can proceed to the next test. If separation occurs, it indicates that the sample is unstable and unsuitable for use as a liquid mulch film adjuvant, and the sample will not proceed to the next test stage.
[0115] 2. The following performance tests were conducted on the garlic residue base film emulsions prepared in Examples 11-14.
[0116] (1) Viscosity test
[0117] The viscosity of the liquids was measured using an NDJ-1 rotational viscometer (Shanghai Nirun Intelligent Technology Co., Ltd., China). During the test, the temperature of each sample was maintained at 30°C, and the rotation speed was controlled at 60 r / min. Viscosity values were recorded in mPa·s.
[0118] (2) Spraying distance test
[0119] The spraying distance performance of liquid samples was tested using a handheld spray gun with an inner diameter of 2.5 mm and an air pressure of 0.3 MPa. The distance that 80% of the emulsion could reach under these conditions was measured. An emulsion with a large spraying distance indicates that the emulsion was sprayed out of the spray gun more smoothly.
[0120] (3) Soil temperature and humidity test
[0121] Soil temperature testing: The soil temperature at a depth of 5 cm in each field in Application Example 10 was measured using a curved tube geothermometer (Beijing Dingsheng Ronghe Technology Co., Ltd., China). The test was conducted from 14:00 to 16:00 every day for 30 days, and the average temperature during this test period was reported as the value.
[0122] Soil moisture content testing: While measuring soil temperature, take 5 grams of soil from a depth of 5 cm in each field and measure the soil moisture content using the drying method. That is, dry the 5 grams of soil at 80℃, and then calculate according to the formula: Soil moisture content = [(5 - mass of dried soil) / 5] × 100%. Test once every 2 days for 30 days. The average soil moisture content during this test period is the reported value.
[0123] (4) Experiment on resistance to diamondback moth
[0124] The diamondback moth resistance test was conducted in a greenhouse environment (25℃, 35% humidity), and the effect of the diamondback moth on the dry weight of Chinese cabbage seedlings was used to represent the resistance. Diamondback moths collected from the farm were first fed with fresh Chinese cabbage for two days to eliminate the influence of the larvae's original food reserves on subsequent experiments. Then, larvae of similar size were selected and divided into several groups of 10 each.
[0125] Small bok choy seedlings of similar weight and appearance were transplanted into several identical flowerpots. Each flowerpot was 20 cm in diameter and 15 cm deep, and contained 2000 g of soil powder obtained by passing through a 5-mesh sieve; each flowerpot contained 7 bok choy seedlings. Then, the high garlic residue content liquid mulch emulsion prepared in Application Examples 11-15 was applied at a rate of 0.58 kg / m³. 2 The appropriate amount of the mulch emulsion was evenly sprayed onto the soil surface of each flowerpot, with flowerpots without any mulch emulsion sprayed (planted only in bare soil) serving as a control group. All flowerpots were placed in the same greenhouse, with one group (10 diamondback moths) placed in each flowerpot. Each flowerpot and the bok choy seedlings in it were completely covered with a white nylon mesh (100 mesh) to prevent the diamondback moths from moving between the seedlings and affecting the experimental results. After 10 days, the damage to the leaves of the bok choy seedlings was observed. Then, the bok choy seedlings, along with their roots, were removed from each flowerpot. The soil attached to the roots was gently removed with a brush, and the seedlings were dried at 80°C for 48 hours. The dried bok choy seedlings in each flowerpot were weighed.
[0126] 3. As can be seen from Table 1, the liquid mulch film adjuvants prepared in Examples 1-5 did not exhibit stratification within 30 days, indicating that the suspensions prepared in Examples 1-5 are stable. In contrast, the liquid sample prepared in Comparative Example 6 showed precipitation, i.e., solid-liquid stratification occurred on day 1. This is because Comparative Example 6 did not use methanol as a solvent, but rather water. The magnesium-aluminum hydrotalcite synthesized in the water solvent is a crystalline solid with high crystal order; the inorganic layers are orderly aggregated and stacked together, resulting in large grains. This can be seen from its X-ray powder diffraction pattern (see attached table). Figure 1a) It was confirmed that the highly ordered stacking of inorganic magnesium-aluminum hydrotalcite layers makes it difficult to suspend in solution, instead existing as a precipitate. This ultimately leads to precipitation and solid-liquid stratification in the liquid mulch emulsion prepared from the sample of Comparative Example 6. If precipitation exists in the liquid mulch emulsion, these precipitate particles will clog the nozzle of the spray gun. Even if a small amount of liquid is sprayed out, the sprayed solid-liquid stratified liquid is difficult to distribute evenly on the soil surface. Therefore, the sample prepared in Comparative Example 6 cannot be used as a liquid mulch adjuvant, and it was not subjected to subsequent testing. The liquid samples prepared in Comparative Examples 7-10 did not exhibit solid-liquid stratification, indicating that the liquid samples prepared in these examples are also stable. This is because comparative examples 7-10 used methanol as a solvent during the preparation process. Methanol molecules, under the action of sodium hydroxide, formed M-OCH3 groups with the metal hydroxyl groups (M-OH) on the magnesium-aluminum hydrotalcite layers. When the magnesium-aluminum hydrotalcite grafted with -OCH3 groups encounters an aqueous solvent, the M-OCH3 groups on the layers are easily hydrolyzed in water to generate M-OH and release CH3OH molecules. This hydrolysis reaction is relatively fast and violent. The energy released by the reaction can instantly depolymerize the magnesium-aluminum hydrotalcite layers and make the magnesium-aluminum hydrotalcite into very small colloidal particles. These tiny colloidal particles can be stably suspended in the aqueous solution without producing solid-liquid stratification.
[0127] As can be seen from the results in Table 2, in Application Example 14, the spraying distance of the garlic residue-based liquid mulch emulsion prepared without any liquid mulch adjuvant was 0 mm. This is because the high garlic residue content in the liquid mulch emulsion without any liquid mulch adjuvant resulted in an excessively high viscosity (1300 mPa·s), making it difficult to spray. The viscosity of the high garlic residue content liquid mulch emulsion prepared with the liquid mulch adjuvants obtained in Examples 1-5 was 210-219 mPa·s, and the spraying distance was 564-573 mm. Obviously, the liquid mulch adjuvants obtained in Examples 1-5 significantly reduced the viscosity of the high garlic residue content liquid mulch emulsion without the adjuvant, allowing the mulch emulsion to be sprayed smoothly. The garlic residue content in the dry weight of the liquid mulch film obtained in Examples 12 and 15 of this invention is much higher than that in the dry weight of the liquid mulch film in Literature 1 (about 22 wt.%). However, the liquid mulch film emulsion with high garlic residue content prepared by the liquid mulch film adjuvants obtained in Examples 1-5 can still be sprayed out smoothly, which also confirms that the liquid mulch film adjuvants obtained in Examples 1-5 do indeed play a role in reducing the viscosity of the liquid mulch film emulsion with high garlic residue content.
[0128] The viscosity of the garlic residue-based liquid mulch emulsion prepared from the mulch film additive (or sample) obtained in Comparative Example 7 was 564 mPa·s (169% higher than the viscosity of the mulch film emulsion in Example 3), and the spraying distance was 201 mm (64.9% lower than the spraying distance of the mulch film emulsion in Example 3). The difference between Comparative Example 7 and Example 3 is that the reaction between sodium unsaturated fatty acids and methoxymagnesium aluminum hydrotalcite was not used, and unsaturated fatty acids-methoxymagnesium aluminum hydrotalcite were not used in the preparation steps. If unsaturated fatty acid ions are embedded between the layers of methoxy-magnesium aluminum layered double hydroxides (LDHs), the interlayer spacing of the LDHs can be increased, reducing the interaction between the layers. This facilitates the subsequent ion exchange reaction between negatively charged carboxyl-modified polyvinyl alcohol (PVA) and the interlayer unsaturated fatty acid ions, allowing it to embed into the LDH layers. The hydroxyl and carboxyl groups of the embedded PVA can interact with the carboxyl and amino groups at the end of the α-amylase molecule through hydrogen bonds, and the negative charge on the amylase can also... The positive charge on the layer of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite intercalation complex interacts with the α-amylase, thereby immobilizing it within a hydrophilic three-dimensional network composed of carboxyl-modified polyvinyl alcohol molecular chains and hydrotalcite layers. This hydrophilic network excludes the fat-soluble allicin from the network, preventing allicin from damaging the α-amylase encapsulated within it. Simultaneously, hydrophilic polysaccharide molecules can enter this hydrophilic network, contact the amylase within it, and be degraded into smaller sugar molecules by the amylase. Because Comparative Example 7 did not yield a carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite intercalation complex, the protective effect of the sample against α-amylase was limited. Furthermore, the highly viscous and hydrophilic polysaccharide molecules were difficult for the amylase to degrade, resulting in a weaker effect of this sample in reducing the viscosity of garlic residue-based liquid mulch film emulsion and increasing the spraying distance of the mulch film emulsion.
[0129] The viscosity of the garlic residue-based liquid mulch film emulsion prepared from the sample obtained in Comparative Example 8 was 603 mPa·s (187% higher than that of the mulch film emulsion in Example 3), and the spraying distance was 182 mm (68.2% lower than that of the mulch film emulsion in Example 3). The difference between Comparative Example 8 and Example 3 is that carboxyl-modified polyvinyl alcohol was not used, i.e., a colloidal suspension of carboxyl-modified polyvinyl alcohol-magnesium-aluminum hydrotalcite was not prepared. Because Comparative Example 8 did not obtain a carboxyl-modified polyvinyl alcohol-magnesium-aluminum hydrotalcite layered composite, similar to Comparative Example 7 above, the protective effect of the sample against α-amylase was limited. Therefore, the viscous and hydrophilic polysaccharide molecules were difficult for amylase to degrade, resulting in a weaker effect in reducing the viscosity of the garlic residue-based liquid mulch film emulsion and increasing the spraying distance of the mulch film emulsion.
[0130] The viscosity of the garlic residue-based liquid mulch film emulsion prepared from the sample obtained in Comparative Example 9 was 482 mPa·s (129% higher than the viscosity of the mulch film emulsion in Example 3), and the spraying distance was 388 mm (32.3% lower than the spraying distance of the mulch film emulsion in Example 3). The difference between Comparative Example 9 and Example 3 is that the mass ratio of the colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite to α-amylase in Comparative Example 9 was 16:1, which is not within the scope of claims (18-21):1. That is, the amount of carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite was relatively small. This resulted in insufficient protection of α-amylase in Comparative Example 9, thus limiting the effect of the sample of Comparative Example 9 in reducing the viscosity of the garlic residue-based liquid mulch film emulsion and increasing the spraying distance of the mulch film emulsion.
[0131] The viscosity of the garlic residue-based liquid mulch emulsion prepared from the sample obtained in Comparative Example 10 was 459 mPa·s (118% higher than the viscosity of the mulch emulsion in Example 3), and the spraying distance was 396 mm (30.9% lower than the spraying distance of the mulch emulsion in Example 3). The difference between Comparative Example 10 and Example 3 is that the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and methanol in step (2) was 1.9:0.6:51, that is, the amount of aluminum nitrate used was less than the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and methanol in the claims, which was (1.4-2.4):1:(46-56). This results in an insufficient number of positive charges on the magnesium-aluminum hydrotalcite inorganic layer, which in turn affects the amount of carboxyl-modified polyvinyl alcohol embedded in the interlayer. In other words, if the content of carboxyl-modified polyvinyl alcohol in the interlayer is too small, the protective effect of the carboxyl-modified polyvinyl alcohol-magnesium-aluminum hydrotalcite interlayer complex on α-amylase is correspondingly weakened. Therefore, the sample obtained in Comparative Example 10 also has limited effect on reducing the viscosity of garlic residue-based liquid mulch film emulsion and increasing the spraying distance of the mulch film emulsion.
[0132] Table 3 shows the viscosity and sprayable distance of the high garlic residue content liquid mulch emulsions prepared using the liquid mulch adjuvant obtained in Example 3 in Application Examples 11-14, as well as the corresponding average soil temperature, average soil moisture content, and the weight of dried Chinese cabbage seedlings in the diamondback moth resistance experiment. The mass ratio of the liquid mulch adjuvant obtained in Example 3 to the garlic residue slurry and starch slurry differs in Application Examples 11-14. The results showed that in application examples 11-13, when the mass ratio of the liquid mulch adjuvant to the garlic residue slurry and starch slurry was within the scope of the claims, the prepared liquid mulch emulsions had similar emulsion viscosity, spraying distance, average soil temperature, average soil moisture content, and the weight of dried bok choy seedlings in the diamondback moth resistance experiment. Compared with bare soil (without any mulch emulsion applied), the liquid mulch prepared in application examples 11-13 increased the soil temperature by at least about 3.3°C, increased the average soil moisture content by at least about 9.4%, and increased the weight of dried bok choy seedlings by at least about 177% in the diamondback moth resistance experiment. This indicates that the liquid mulch prepared in application examples 11-13 has a significant effect on increasing soil temperature and soil moisture, and that the high garlic residue content in the liquid mulch effectively prevents diamondback moths from consuming bok choy leaves.
[0133] Compared to Application Example 12, the liquid mulch emulsion in Application Example 14 had a viscosity of 410 mPa·s (95% higher than that in Application Example 12) and a spraying distance of 401 mm (30% less than that in Application Example 12). Furthermore, compared to Application Example 12, Application Example 14 also showed a 3.52°C lower average soil temperature, a 5.5% lower average soil moisture content, and a 34.3% lower weight of dried bok choy seedlings in the diamondback moth resistance experiment. The difference between Application Example 14 and Application Example 11 is that in step (S1), the mass ratio between the liquid mulch film adjuvant prepared in Example 3, the garlic residue slurry, and the starch slurry is 0.06:1:1. That is, the amount of liquid mulch film adjuvant is lower than the range of claims (0.08-0.15):(0.9-1.1):1. Obviously, the low amount of liquid mulch film adjuvant weakens its effect in reducing the viscosity of garlic residue-based liquid mulch film emulsion and increasing the spraying distance of mulch film emulsion. It also reduces its soil heat preservation, water retention and pest resistance performance.
[0134] Table 1 shows the stability of the liquids obtained in Examples 1-5 and Comparative Examples 6-10, which was evaluated by recording whether the liquids exhibited stratification within 30 days.
[0135]
[0136] Table 2 shows the viscosity and sprayable distance of the liquid mulch film emulsions prepared in Application Examples 12 and 15. Example 3 in the table represents the mulch film emulsion prepared using the mulch film additives obtained in Example 3, and so on.
[0137]
[0138] Table 3 shows the viscosity and sprayable distance of the high-garlic-residue-content liquid mulch emulsions prepared using the liquid mulch adjuvant obtained in Example 3 in Application Examples 11-14, along with the corresponding average soil temperature, average soil moisture content, and the weight of dried bok choy seedlings in the diamondback moth resistance experiment. Bare soil (without any mulch emulsion applied) is used as a comparison. In the table, Example 11 represents the liquid mulch prepared using the rheology modifier obtained in Example 3 in Application Example 11, and so on.
[0139]
Claims
1. A method for preparing a liquid mulch film adjuvant with high garlic residue content, the preparation steps of which are as follows: (1) Dissolve NaOH in methanol at 45-55℃ to obtain solution A, wherein, The weight ratio of NaOH to methanol is 1:(5-6.7); (2) At room temperature, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate are dissolved in methanol to obtain solution B, wherein the weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and methanol is (1.4-2.4):1:(46-56); (3) Add the solution B obtained in step (2) dropwise to the solution A obtained in step (1) at 45-55℃ and stirring at 2000-5000r / min. The dropwise rate is 1 drop every 3-5 seconds. When the pH of the resulting mixture is 7.5-8.5, the dropwise addition ends. Continue the reaction for 10-24 hours, and then obtain a white mixture C. (4) Heat the white mixture C obtained in step (3) to 55-65℃, add sodium unsaturated fatty acid, and then stir at a speed of 1000-3000 r / min for 3-12 h to obtain a white mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite, wherein the weight ratio of the white mixture C obtained in step (3) to sodium unsaturated fatty acid is (6-15):(0.28-0.58); (5) Filter the mixture D containing unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite obtained in step (4), and wash the filtered gel with methanol solvent 3-5 times to obtain white unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E, wherein the weight ratio of mixture D to methanol solvent is 1:
3. (6) Dissolve carboxyl-modified polyvinyl alcohol in water at room temperature to obtain solution F. Then adjust the pH of solution F to 6.5-7.5 with sodium hydroxide solution. Then add the unsaturated fatty acid-methoxy magnesium aluminum hydrotalcite gel E obtained in step (4) to solution F under stirring conditions at 20-35℃. The stirring speed is 2500-5000 r / min. After stirring for 6-24 h, a colloidal suspension G containing carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite intercalated organic-inorganic composite is obtained. The weight ratio of carboxyl-modified polyvinyl alcohol to water in solution F is (0.5-1.5):100, the mass percentage concentration of sodium hydroxide solution is 2%-5%, and the weight ratio of solution F to gel E is (1.5-3.5):
1. (7) The colloidal suspension G of the carboxyl-modified polyvinyl alcohol-magnesium aluminum hydrotalcite layered intercalation organic-inorganic complex obtained in step (6) is stirred with α-amylase at room temperature for 1-5 hours at a stirring speed of 100-500 r / min. The resulting colloidal suspension is a garlic residue-based liquid mulch adjuvant with high garlic residue content. The mass ratio of colloidal suspension G to α-amylase is (18-21):
1.
2. The preparation method according to claim 1, wherein, The weight ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and methanol in step (2) is 1.9:1:
51.
3. The preparation method according to claim 1, wherein, The white mixture C obtained in step (3) in step (4) has a weight ratio of 10:0.4 to sodium unsaturated fatty acids.
4. The preparation method according to claim 1, wherein, The weight ratio of solution F to gel E in step (6) is 2.5:
1.
5. The preparation method according to claim 1, wherein, The mass ratio of colloidal suspension G to α-amylase in step (7) is 19.5:
1.
6. A method for preparing a liquid mulch film with high garlic residue content, characterized in that, The raw materials used in the liquid mulch film include: the high garlic residue content liquid mulch film additive as described in any one of claims 1-5, garlic residue slurry, starch slurry, and a mixture of acrylic monomers. The preparation steps are as follows: (S1) A liquid mulch film additive with high garlic residue content is stirred with garlic residue slurry at 55-65℃ for 0.5-1.5h at a speed of 50-150r / min. The resulting mixture is then mixed with starch slurry and stirred at 55-65℃ for 1.5-3h at a speed of 50-150r / min to obtain slurry J. The garlic residue slurry contains garlic residue particles smaller than 10 mesh, and the weight content of garlic residue in the slurry is 65-75%. The starch slurry is prepared from soluble starch, and the mass ratio of soluble starch to water is (0.15-0.21):
1. The mass ratio of the liquid mulch film additive, garlic residue slurry, and starch slurry is (0.08-0.15):(0.9-1.1):
1. (S2) The J slurry obtained in step (S1) is mixed with an acrylic monomer mixture, an emulsifier, and water. The resulting mixture is pre-emulsified at 70-80℃ and a stirring speed of 1500-3500 r / min for 30-120 min to obtain a pre-emulsified mixture K. The mass ratio of the J slurry, the acrylic monomer mixture, the emulsifier, and water is (15-22):(4-10):1:(14-28). The acrylic monomer mixture includes butyl acrylate, methyl methacrylate, and acrylic acid, and the mass ratio of the three is (6.5-7.5):(1.5-2.5):
1. (S3) While stirring at 75-90℃, add the initiator aqueous solution dropwise to the pre-emulsified mixture K obtained in step (S2) at a rate of 0.2-1.5 mL / min. The stirring speed is 250-500 r / min. After the initiator is added, continue the reaction for 2-8 h. The mass ratio between the pre-emulsified mixture K and the initiator aqueous solution is (6.5-8.5):
1. Then, cool the reaction system to room temperature and adjust the pH of the system to 6.8-7.5 with ammonia.
7. The preparation method according to claim 6, wherein, The acrylic monomer mixture mentioned in preparation step (S2) includes butyl acrylate, methyl methacrylate and acrylic acid, wherein the mass ratio of the three is 7.0:2.0:1; the emulsifier is a mixture of reactive emulsifier and octylphenol polyoxyethylene ether (10), wherein the mass ratio of the two is 1:(2.5-3.5), and the reactive emulsifier is of type LRS-10.
8. The preparation method according to claim 6, wherein, The initiator aqueous solution mentioned in preparation step (S3) is a potassium persulfate or ammonium persulfate aqueous solution, wherein the mass concentration of potassium persulfate or ammonium persulfate is 3.5-5.5%, and the mass percentage concentration of ammonia water is 25%.
9. The preparation method according to any one of claims 1-8, characterized in that, The water used is deionized water.
10. The application of the high garlic residue content liquid mulch film prepared by the preparation method according to any one of claims 6-8 in the field of agricultural liquid mulch film.
Citation Information
Patent Citations
Garlic extract based insect-resistant mulching film and preparation method thereof
CN114561033A
Preparation method of garlic residue-starch-based liquid mulching film
CN115181301A